Occult HIV-1 drug resistance to thymidine analogues following failure of first-line tenofovir combined with a cytosine analogue and nevirapine or efavirenz in sub Saharan Africa: a retrospective multi-centre cohort study. Issue 3 (March 2017) - Gregson, John; Kaleebu, Pontiano; Marconi, Vincent C; van Vuuren, Cloete; Ndembi, Nicaise; Hamers, Raph L; Kanki, Phyllis; Hoffmann, Christopher J; Lockman, Shahin; Pillay, Deenan; de Oliveira, Tulio; Clumeck, Nathan; et al.
Summary: Background: HIV-1 drug resistance to older thymidine analogue nucleoside reverse transcriptase inhibitor drugs has been identified in sub-Saharan Africa in patients with virological failure of first-line combination antiretroviral therapy (ART) containing the modern nucleoside reverse transcriptase inhibitor tenofovir. We aimed to investigate the prevalence and correlates of thymidine analogue mutations (TAM) in patients with virological failure of first-line tenofovir-containing ART. Methods: We retrospectively analysed patients from 20 studies within the TenoRes collaboration who had locally defined viral failure on first-line therapy with tenofovir plus a cytosine analogue (lamivudine or emtricitabine) plus a non-nucleoside reverse transcriptase inhibitor (NNRTI; nevirapine or efavirenz) in sub-Saharan Africa. Baseline visits in these studies occurred between 2005 and 2013. To assess between-study and within-study associations, we used meta-regression and meta-analyses to compare patients with and without TAMs for the presence of resistance to tenofovir, cytosine analogue, or NNRTIs. Findings: Of 712 individuals with failure of first-line tenofovir-containing regimens, 115 (16%) had at least one TAM. In crude comparisons, patients with TAMs had lower CD4 counts at treatment initiation than did patients without TAMs (60·5 cells per μL [IQR 21·0–128·0] in patients with TAMS vs 95·0 cells per μL [37·0–177·0] in patients without TAMs; p=0·007) and were more likely to have tenofovir resistance (93 [81%] of 115 patients with TAMs vs 352 [59%] of 597 patients without TAMs; p<0·0001), NNRTI resistance (107 [93%] vs 462 [77%]; p<0·0001), and cytosine analogue resistance (100 [87%] vs 378 [63%]; p=0·0002). We detected associations between TAMs and drug resistance mutations both between and within studies; the correlation between the study-level proportion of patients with tenofovir resistance and TAMs was 0·64 (p<0·0001), and the odds ratio for tenofovir resistance comparing patients with and without TAMs was 1·29 (1·13–1·47; p<0·0001) Interpretation: TAMs are common in patients who have failure of first-line tenofovir-containing regimens in sub-Saharan Africa, and are associated with multidrug resistant HIV-1. Effective viral load monitoring and point-of-care resistance tests could help to mitigate the emergence and spread of such strains. Funding: The Wellcome Trust.